Transforming Educational Accountability in Medical Ethics and Humanities Education Toward Professionalism. (June 2015) - Doukas, David J.; Kirch, Darrell G.; Brigham, Timothy P.; Barzansky, Barbara M.; Wear, Stephen; Carrese, Joseph A.; Fins, Joseph J.; Lederer, Susan E.
Abstract : Effectively developing professionalism requires a programmatic view on how medical ethics and humanities should be incorporated into an educational continuum that begins in premedical studies, stretches across medical school and residency, and is sustained throughout one's practice. The Project to Rebalance and Integrate Medical Education National Conference on Medical Ethics and Humanities in Medical Education (May 2012) invited representatives from the three major medical education and accreditation organizations to engage with an expert panel of nationally known medical educators in ethics, history, literature, and the visual arts. This article, based on the views of these representatives and their respondents, offers a future-tense account of how professionalism can be incorporated into medical education. The themes that are emphasized herein include the need to respond to four issues. The first theme highlights how ethics and humanities can provide a response to the dissonance that occurs in current health care delivery. The second theme focuses on how to facilitate preprofessional readiness for applicants through reform of the medical school admission process. The third theme emphasizes the importance of integrating ethics and humanities into the medical school administrative structure. The fourth theme underscores how outcomes-based assessment should reflect developmental milestones for professional attributes and conduct. The participants emphasized that ethics and humanities-based knowledge, skills, and conduct that promote professionalism should be taught with accountability, flexibility, and the premise that all these traits are essential to the formation of a modern professional physician.